Income Shocks, Bride Price and Child Marriage in Turkey - Isabelle Chort; Rozenn Hotte; Karine Marazyan (Institute of Labor Economics (IZA), 2022)
This paper investigates the impact of income shocks and bride price on early marriage in Turkey. The practice of bride-price, still vivid in many regions of the country, may provide incentives for parents to marry their daughter earlier, when faced with a negative income shock. In addition, marriages precipitated by negative income shocks may present specific features (endogamy, age and education difference between spouses). Weather shocks provide an exogenous source of variation of household income through agricultural production. Data on weather shocks are merged with individual and household level data from the Turkish Demographic and Health Surveys 1998 to 2013. To study the role of payments to the bride's parents, we interact our measure of shocks with a province-level indicator of a high prevalence of bride-price. We find that girls living in provinces with a high practice of bride-price and exposed to a negative income shocks when aged 12-14 have a 28% higher probability to be married before the age of 15 than girls not exposed to shocks. This effect is specific to provinces with a high prevalence of bride price. Compared to women who experienced the same shock but lived in a province where bride price is infrequent, such women are also more likely to give birth to their first child before 18 and for those who married religiously first, the civil ceremony is delayed by 2 months on average. Our results suggest that girl marriage still participates to household strategies aimed at mitigating negative income shocks in contemporary Turkey.
Keywords: J1; J12; J13; O15; 330; cultural norms; child marriage; bride price; weather shocks; Turkey